Correlation analysis of electric field and electron density fluctuations observed by a sounding rocket S-310JA-7 - Mori, Hirotaka; Sagawa, Eiichi; Ogawa, Tadahiko; Ogawa, Toshio; Yamagishi, Hisao (1985)
P(論文) A Faraday cup and a pair of double probes on board a rocket S-310JA-7 observed simultaneously intense quasi-sinusoidal waves, frequency of which was near the local ion cyclotron frequency over the E layer of the auroral region ionosphere. By a cross-correlation analysis of the both measurements, it is found that the frequency of the waves observed by the double probes is constantly lower by the rocket spin frequency than the frequency of the same waves observed by the Faraday cup. This result suggests that the waves have right-hand circularly or elliptically polarized electric fields. departmental bulletin paper